2009
DOI: 10.1158/0008-5472.can-09-1778
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Collapsin Response Mediator Protein1, as Detected by iTRAQ Analysis, Promotes Invasion of Human Gliomas Expressing Mutant EGFRvIII

Abstract: Glioblastoma multiforme (GBM) is the most common and lethal primary human brain tumor. GBMs are characterized by a variety of genetic alterations, among which oncogenic mutations of epidermal growth factor receptor (EGFRvIII) is most common. GBMs harboring EGFRvIII have increased proliferation and invasive characteristics versus those expressing wildtype (wt) EGFR. To identify the molecular basis of this increased tumorgenic phenotype, we used iTRAQ-labeling differential proteomic analysis. Among several diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Using data recorded from isolated single cells for comparison, the twocell data exhibits clear repression of EGFR signaling at small cell separations (<80 μm), and elevated EGFR signaling at larger separations (>100 μm) (12). Elevated levels of phosphoproteins downstream of EGFR have been associated with enhanced tumorigenicity and motility (2,(5)(6)(7)(8). Thus, the data implies a relationship between tumorigenic activity and cell separation.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Using data recorded from isolated single cells for comparison, the twocell data exhibits clear repression of EGFR signaling at small cell separations (<80 μm), and elevated EGFR signaling at larger separations (>100 μm) (12). Elevated levels of phosphoproteins downstream of EGFR have been associated with enhanced tumorigenicity and motility (2,(5)(6)(7)(8). Thus, the data implies a relationship between tumorigenic activity and cell separation.…”
Section: Resultsmentioning
confidence: 91%
“…In every biological replicate 900 ≤ N ≤ 1,900 cell pairs were found that had a separation distance of ≤200 μm and were used to calculate RDF and uðrÞ functions. in increased downstream signaling (21) and enhanced invasiveness and cell motility (2,7,22). Recently, a unidirectional cross-talk between EGFRvIII+ and wtEGFR cells was revealed within a heterogeneous GBM tumor; EGFRvIII+ cells were able to induce EGFR signaling through IL-6 in U87wtEGFR cells but not vice versa (1).…”
Section: Predicting Spatial Distributions Of Gbm Cells From the Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…43 CRMP1 has a role in SEMA3A-(a gene associated with AD 44 ) mediated regulation of neural growth and axonal guidance, and microtubule assembly. 43,[45][46][47] Considering the role of CRMPs in axonal guidance and regeneration in the brain, gain in CRMP1 could compromise neuroplasticity with aging and thus lead to AD. Interestingly, CRMP2 has been reported to be hyper-phosphorylated as an early event in AD pathogenesis.…”
Section: Rare Autosomal Cnvs In Eo-fad Bv Hooli Et Almentioning
confidence: 99%
“…11-18 CRMP1 suppressed invasion and was correlated with clinical outcomes in non-small cell lung cancer and glioblastoma. [12][13][14][15] Gao et al 18 found that CRMP4 expression was inversely associated with lymph node metastasis from prostate cancer. In vitro studies of pulmonary cancer showed that Sema3A was endowed with putative antitumor activity.…”
mentioning
confidence: 99%